1998
DOI: 10.1002/1529-0131(199807)41:7<1203::aid-art9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biochemical markers of joint tissue metabolism in a randomized controlled trial of glucocorticoid in early rheumatoid arthritis

Abstract: Objective. To determine the effects of low-dose prednisolone on joint tissue metabolism in early rheumatoid arthritis (RA).Methods. In addition to a range of biochemical markers of cartilage, bone and synovial tissue turnover, levels of pro-matrix metalloproteinase 3 (pro-MMP3), pro-MMP-1, and cytidine deaminase (CD) were measured in serum from 79 of 128 patients with early RA who took part in the Arthritis and Rheumatism Council Low-Dose Glucocorticoid Study. Serum concentrations of joint tissue metabolites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…19,20 A possible correlation between steroid therapy and MMP-3 levels was examined in patients in the present study. All patients with active disease and 4 of 14 patients in remission received corticosteroids.…”
Section: Discussionmentioning
confidence: 95%
“…19,20 A possible correlation between steroid therapy and MMP-3 levels was examined in patients in the present study. All patients with active disease and 4 of 14 patients in remission received corticosteroids.…”
Section: Discussionmentioning
confidence: 95%
“…21 Sharif et al observed a doubling of serum MMP-3 levels in patients with rheumatoid arthritis (RA) who were administered 7.5 mg of prednisolone daily, whereas the clinical and biological parameters of RA disease activity decreased with the treatment. 22 Measuring MMP-3 to assess TA disease activity should be done with caution. Among these new biomarkers, PTX3 was the most reliable single marker for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of PSL for three months increases serum MMP-3 levels in the cases of lupus nephritis (9). In RA, low-dose PSL treatment over 2 years may also increase serum pro-MMP-3 (proenzyme form of MMP-3) levels although synovium-derived markers such as hyaluronate decrease suggesting the remission of the articular synovitis (11). According to these findings, the serum pro-MMP-3 level may be increased by changes of joint tissue metabolism due to PSL therapy despite the fact the therapy ameliorates the synovitis (11).…”
Section: Discussionmentioning
confidence: 99%